Effect of Different Pellet Binders on Palm Kernel on Growth Performance and Nutrient Digestibility in Broiler Chicken - Marfuah, Nuun; Sundu, Burhanudin; Rusdi, Rusdi; Sugiarto, Sugiarto (Jurnal Ilmu Ternak Universitas Padjadjaran, 2026)
Feed plays a paramount role in supporting growth, metabolism, and production performance. Their high price encourages the utilization of inexpensive and alternative feed ingredients. PKM, one such feed ingredient, is produced by palm oil industries. However, there is still a very limited application because of its high crude fiber content, which needs processing technologies like pelletization with binder addition. Based on this background, this experiment has been conducted to study the effect of various types of natural and commercial binders in 15% PKM-based pellets on performance and nutrient digestibility of broilers. The study was done for five weeks using 150 DOC broiler chickens of the CP 707 strain arranged in a completely randomized design with seven treatments and five replications. Observed variables are feed consumption, body weight gain, feed conversion ratio, crude protein digestibility, and metabolizable energy digestibility. The results showed that the use of PKM pellets with a binder significantly affected the growth and digestion of the broiler chickens. The best results were obtained when starch was used as a binder in pellet treatment. On this basis, starch is recommended as a binder for the preparation of 15% PKM pellets, which would contribute towards sustainable efficiency in the use of feed.